Świadkowie czynności egzekucyjnych - Knoppek, Krzysztof (Wydział Prawa i Administracji UAM, 1991)
The article presents legal character of the institution of witnesses for acts in executory proceedings. The author proves that such witnesses should be included into the category of witnesses appointed to legal transactions. The provisions of the Code of Civil Procedure on evidence by witness do not apply to witnesses for acts in executory proceedings, even though one of the functions of witnesses for acts in executory proceedings in securing the evidence for judicial proceedings which may be started in connection with the executory acts performed. The participation of witnesses in executory acts does not take place "ad solemnitatem", but is of great significance from the point of view of correctness and openness of acts carried out by a court executive officer. The article also contains considerations on practical aspects of the participation of witnesses in executory acts.
Witnesses for acts in executory proceedings